What is successful aging?: a psychometric validation study of different construct definitions - Kleineidam, Luca; Weyerer, Siegfried; Werle, Jochen (The gerontologist, 2019)
We examined the validity of 5 successful aging (SA) operationalizations that assessed different facets of the SA construct (cognitive and physical health and disability; well-being; social engagement).